Discovery and Re-discovery of Antibiotics : A Further Study - Neelameghan, A.; Ravichandra Rao, I. K.; Gupta, B. S. S. (Journal of Information and Knowledge, 1972)
The linear relation between the number of discoveries and the number of re-discoveries in the field of antibiotics conforms to the Square-Cube Law as applied to growing organisms. The Square-Cube Law relation gives a rriore precise prediction of the number of rediscoveries of antibiotics given the number of reports of discoveries of antibiotics, than with the least square technique, reported earlier. There is isometry between the relative rate of growth of the cumulative total number of discoveries and the cumulative total of the number of re-discoveries.